Orienting global surgery initiatives toward advancing minimally invasive surgery in Africa: a commentary based on continent-wide reviews - Adebayo Falola; Abdourahmane Ndong; Ademola Adeyeye (BMC Surgery)
Abstract Surgical care has advanced with the introduction of minimally invasive surgery (MIS) techniques, which have resulted in a reduced length of hospital stay and improved patient outcomes with regard to morbidity, mortality, and aesthetics. Implementation in Africa remains limited due to economic, infrastructural, and training-related issues. Our previous reviews show that adoption of MIS in Africa has been highly variable. Only Egypt and South Africa, for example, have significantly reported robotic surgery programs. Despite present challenges, recent developments show that progress is being made. Advantages of MIS in resource-limited settings include fewer postoperative complications and shorter hospital stays, crucial for African patients who cannot afford unexpectedly extensive postoperative care and are also reliant on daily earnings. In the future, tele-robotic surgery can improve access to surgical care in under-served regions of the continent. Implementation barriers include the high cost of equipment, inadequate healthcare infrastructure, and limited training opportunities. Investment in the development of low-cost innovations, such as MIS equipment suited for resource-limited settings, local manufacturing or assembly of MIS equipment, and the establishment of training programs within the continent, is necessary to overcome these challenges. Policies supporting the integration of MIS into national healthcare plans are also required. The development of more robust MIS programs in Africa will not only enhance surgical care but will also contribute to the improvement of healthcare and economic outcomes across the continent. We present this commentary on the current state, challenges, and opportunities for the wider adoption of MIS across Africa, based on recent continent-wide reviews.